Update About The Changes In Bacterial Resistance For Multiple Antibiotic In Patients With Urinary Tract Infection In Kerbala: Pembaruan Tentang Perubahan Resistensi Bakteri Untuk Beberapa Antibiotik Pada Pasien Infeksi Saluran Kemih Di Kerbala - Kawther Mohammed Radah Ali (Academia Open, 2024)
Urinary tract infections (UTIs) caused by Escherichia coli (E. coli) are common and recurrent, particularly among females. Treatment often involves various antimicrobial agents, but rising resistance poses challenges. We conducted a study in Al-Hussein Medical City, Kerbala, enrolling 520 UTI patients from April 2022 to February 2023. Urine samples were tested for antimicrobial susceptibility. Results showed high resistance to most agents, except meropenem and levofloxacin. Our findings emphasize the urgent need for strategies to combat antimicrobial resistance in UTIs. Highlights: High resistance in UTI treatment observed. Urgent need for antimicrobial resistance strategies. Study reveals E. coli resistance patterns in Kerbala's medical setting. Keywords: Urinary tract infections, Escherichia coli, Antimicrobial resistance, Al-Hussein Medical City, Kerbala